A novel bacteriocin from Lactobacillus salivarius against Staphylococcus aureus: Isolation, purification, identification, antibacterial and antibiofilm activity. (April 2021) - Li, Hong-Wei; Xiang, Yi-Zhou; Zhang, Man; Jiang, Yu-Hang; Zhang, Yao; Liu, Ying-Yang; Lin, Lian-Bing; Zhang, Qi-Lin
Abstract: Bacteriocins are known to inhibit various foodborne bacteria and their biofilms; however, few bacteriocins with activity against food-derived Staphylococcus aureus have been reported. Here, a novel bacteriocin ( XJS01 ) from the Lactobacillus salivarius strain CGMCC2070 was obtained, purified, and extensively characterized. Molecular mass and amino acid composition of XJS01 were 666.31 Da and F–S-G-L-A-G-D, respectively. XJS01 inhibited the S. aureus strain 2612:1606BL1486 ( S. aureus _26), which was originally isolated from chicken meat. Also, XJS01 showed good resistance to heat treatment, and was only susceptible to pepsin treatment. The minimum inhibitory concentration of XJS01 against S. aureus_ 26 was 9.85 μg/mL, which is lower than previously reported levels for most described bacteriocins. Furthermore, exposure to XJS01 also decreased viability and significantly inhibited ( p  < 0.05) planktonic S. aureus _26 cells. Biofilm formation of S. aureus _26 was also significantly inhibited ( p  < 0.05). The results of electron microscopy showed that XJS01 impaired membrane permeability in S. aureus_ 26, caused leakage of cytoplasmic content, and led to cell deformation. In summary, this study identifies the bacteriocin XJS01 as a potentially candidate for the control of S. aureus in foods in either planktonic or biofilm states. Highlights: A novel bacteriocin designated as XJS01 was purified and characterized. Molecular mass and amino acid composition of the bacteriocin were revealed. The bacteriocin reduce viability and promote death of planktonic S. aureus cells. The biofilm formation is inhibited after bacteriocin treatment. The bacteriocin cause permeability and deformation of S. aureus cells.